NEGOTIATING IDENTITY ACROSS BORDERS: ALIENATION AND ESTRANGEMENT IN AND THE MOUNTAINS ECHOED - Walunj, Jyoti Dnyaneshwar; Gadekar, Sachin (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This paper examines the pervasive themes of alienation, identity crisis, estrangement, and uprootedness in contemporary literature, with particular focus on And the Mountains Echoed (2013) by Khaled Hosseini. It explores how displacement and relocation contribute to a sense of unhomeliness, causing individuals to feel like outsiders in unfamiliar cultural settings. The study highlights how migrants often struggle with a fractured identity, caught between multiple cultural frameworks, which results in emotional and psychological dislocation. By analyzing key characters and narrative strands in the novel, the paper demonstrates how Hosseini portrays the inner conflicts of individuals negotiating belonging, memory, and cultural hybridity. Ultimately, the research underscores the complex relationship between migration, identity, and alienation in a globalized world.